A Further Enhancement of Gale - Shapley Algorithm Applied to course preference incoming PLM Freshmen Students - Rodel B. Bernarbe; Knedrich Karl B. Luna and Edrianne T. Reyes. 4 0 16; 5 (2012)
u
Undergraduate Thesis (BS Computer Science) - Pamantasan ng Lungsod ng Maynila, 2012.
Keywords: 2 -- 0; 6; 20; 20; 2